Low-level HIV viremia is associated with low antiretroviral prescription refill rates and social deprivation. Issue 11 (2nd November 2021) - Goupil de Bouillé, Jeanne; Collignon, Marion; Capsec, Jean; Guillon, Leslie; Le Moal, Gwenael; Barin, Francis; Roncato, Mariam; Hocqueloux, Laurent; Stefic, Karl; Bernard, Louis; Gras, Guillaume
ABSTRACT: Optimal management of patients experiencing persistent low-level viremia (LLV) remains challenging and poorly understood. This study aimed to assess the association between poor antiretroviral treatment (ARV) adherence and persistent LLV. ADHELOW is a sub-study of the ECHEC cohort comprising HIV-infected adults with virological failure (viral load>50 copies/mL). Patients were recruited in 2013–2015 from 4 French university hospitals. Those with LLV (i.e., ≥2 viral load measurements between 50 and 500 copies/mL) were selected and matched on age and sex to 3 controls with virological suppression. The adherence rate was estimated using pharmacy-delivered prescription refills over one year. Overall, 60 patients were included (15 LLV and 45 controls). Mean age was 50.20 years, M/F sex ratio was 14 and mean EPICES (social deprivation) score was 42.90. In univariable analyses, LLV patients had significantly lower adherence (<80%: 53.30% vs. 6.67%, p  < 0.01) and were more likely to have an EPICES score >40.2 (60.00% vs. 24.44%, p  < 0.01). In multivariable analysis, these two variables remained significantly associated with LLV (OR 31.49, CI 95% [4.54–218.70]) and OR 11.00 (CI 95% [1.87–218.70], respectively). Poor long-term treatment adherence, estimated by prescription refills, was strongly associated with LLV. This reinforces the message that adherence counseling should be the primary intervention to overcome LLV.